2006
DOI: 10.1080/09638280500404362
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with sexual life among persons with traumatic spinal cord injury and meningomyelocele

Abstract: The results corroborate findings from earlier studies that satisfaction with sexual life is rather low among persons with SCI. Especially ageing men with traumatic SCI who have sustained injury at an older age are a challenge for rehabilitation. The high satisfaction with sexual life in the women in comparison with the men with MMC is a finding not reported earlier. Our results suggest that adequate treatment of incontinence and pain might improve even sexual satisfaction. Sexual counselling should be given to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 38 publications
7
35
1
3
Order By: Relevance
“…It is therefore to be expected that many people with SB will be reluctant to initiate sexual relationships (19). urinary incontinence has been associated with sexual malfunctioning (19,27), whereas another study did not find any correlation between urinary or faecal incontinence and satisfaction with sexual life (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore to be expected that many people with SB will be reluctant to initiate sexual relationships (19). urinary incontinence has been associated with sexual malfunctioning (19,27), whereas another study did not find any correlation between urinary or faecal incontinence and satisfaction with sexual life (28).…”
Section: Discussionmentioning
confidence: 99%
“…The response rate of 74% is regarded as good, compared with similar studies that have reported participation rates of 24.8-71.6% (8,19,13,23,28). In addition, there was no significant difference between participants and non-participants in terms of gender and age.…”
Section: Representativeness and Limitationsmentioning
confidence: 92%
“…Factors affecting quality of life include the patient's relationship with their partner 46 and, in men, the inconvenience of urinary incontinence is associated with sexual dissatisfaction. 52 Successful bladder management can make a big difference to the patient's sex life and, hence, quality of life. A questionnaire survey of men (aged 18--66 years) with spinal cord injury found that sexual activity was significantly more common in those able to perform intermittent self-catheterization.…”
Section: The Impact Of Neurogenic Bladder On Quality Of Lifementioning
confidence: 99%
“…On bir tetraplejik hastamızın tamamı aynı zamanda el fonksiyonlarını yetersiz olarak bildirmişlerdir. Spinal kord yaralanmalı hastalarda seksüel aktivitede anlamlı azalma olur (13). En önemli faktörler, erektil disfonksiyon ve bozulmuş ejakülasyon olarak rapor edilmiştir (14).…”
Section: Discussionunclassified